Influence of the homogenization pressure on the ice cream mix quality - Iva Murgić; Rajka Božanić (Mljekarstvo)
In this paper the suitability of different homogenization pressures on appearance and quality of ice cream mix was determined. The ice cream mix were taken from ageing tank, and depending on the source of fat in ice cream mix (butter, vegetable fat or cream) they were homogenized under different pressures. Afterwards, by microscope with scalar, fat globule size was determined. The homogenization pressures reduce the fat globule size to 1-2 μm without clumping and these pressures have been characterized as adequate pressures for specific type of fat and specific portion of fat in the ice cream mixture. The higher the fat in the mixture, the lower the pressure should be. The optimal pressure for ice cream mixture containing 2% vegetable fat was 200 bars, for 6% 190-200 bars, and for 8% 170 bars. The optimal pressure for ice cream mixture that contained 8% butter was 190-200 bars, for 10% 150, and for 12% 135 bars. For ice cream mixture containing 8% of cream, optimal pressure was 200 bars, 10% cream was 190, 12% cream was 125 bars and 14% cream was 90 bars.